Bagaimana Perhitungan Unit Cost Kamar Hotel Melalui Pendekatan Metode Tradisional dan Activity Based Costing? - Hendra Gunawan; Stefania Fatma (Politeknik Negeri Batam, 2015)
The research discusses how the calculation and comparison of cost hotel rooms using traditional methods and activity based costing approach. The research uses data collection techniques case studies by observation and interview at a hotel and were analyzed descriptively. These results indicate that the determination of tariffs traditionally only allocate unit costs into one cost driver resulting in a lower cost for the kind of room with a high rate. Activity based costing method approach resulted in a lower room cost for this type of room with a low rate because the cost of each activity charged to the many cost driver. In addition to the activity based costing is able to properly allocate costs based on consumption activity of each activity.